Analisis Penerapan Pembelajaran Fiqih berbasis Higher Order Thinking Skill (HOTS) di MAN Kota Pasuruan - Lilawati, Emi; Fatimah, Siti (JoEMS (Journal of Education and Management Studies), 2023)
Hots-based learning in the subject of Jurisprudence is learning that requires the ability to think critically, logically, reflectively, metacognitively, and think creatively about fiqh materials. The purpose of this study was to describe the application of High Order Thinking Skills (Hots)-based fiqh learning at MAN Kota Pasuruan. This research is a descriptive qualitative research. The number of informants in this study were 5 grade XI students, grade XI fiqh teachers and madrasah curriculum deputy head. The data collection techniques used were observation, interview, and documentation. Descriptive type qualitative data analysis technique through four stages, namely data reduction, data display and conclusion/verification. Data validation techniques use trustworthiness, extension of participation and triangulation. The results showed that: The implementation of High Order Thinking Skills (Hots) based fiqh learning at MAN Kota Pasuruan has been effective since the establishment of the 2013 curriculum until now. The purpose of implementing Higher Order Thinking Skills (Hots) learning in fiqh subjects is to improve and develop the ability of thinking patterns and the ability of students at a higher level in learning Fiqh with discussion, question and answer and problem solving methods. While the obstacles in its application are the teacher's difficulty in dealing with the different abilities of students, the less than optimal preparation of students in learning fiqh.